2019
DOI: 10.33607/bjshs.v3i114.805
|View full text |Cite
|
Sign up to set email alerts
|

Links between Adolescents’ Health Literacy and their Physical Activity and Body Mass Index

Abstract: Background. The aim of the study was to identify links between health literacy, health information literacy and physical activity as well as body mass index in adolescents.Methods. The study was carried out from September till the end of November, 2018. Research participants were 167 14–18-year-old students from Kaunas, Klaipeda and Vilnius (n = 107 females, n = 60 males). Participants were asked to fill in an anonymous online questionnaire, which consisted of basic demographics, physical activity, health info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Paakkari et al 20 found higher health literacy among adolescents participating in sports club activities. To the contrary, Rutkauskaitė and Kuusinen 24 found no link between health literacy and physical activity. Adolescents maintain the health behaviors and habits they acquired during their adolescence throughout their lives.…”
Section: Discussionmentioning
confidence: 93%
“…Paakkari et al 20 found higher health literacy among adolescents participating in sports club activities. To the contrary, Rutkauskaitė and Kuusinen 24 found no link between health literacy and physical activity. Adolescents maintain the health behaviors and habits they acquired during their adolescence throughout their lives.…”
Section: Discussionmentioning
confidence: 93%
“…Für Rauchen und Sport zeigen sich die Gesundheitskompetenzdimensionen Kommunikations-und Interaktionsfähigkeiten und Einstellung zu Gesundheit und Gesundheitsinformationen als bedeutsam. Andere Studien fanden auch positive Assoziationen zwischen Rauchen oder Sport und Gesundheitskompetenz, aber untersuchten nicht die beiden hier diskutierten Dimensionen oder nutzten andere Indikatoren für körperliche Aktivität [2,17,22]. Die in unserer Studie gefundenen Ergebnisse liefern damit die ersten detaillierten Ergebnisse zur Gesundheitskompetenz und vier Indikatoren des Gesundheitsverhaltens Jugendlicher in Deutschland.…”
Section: Diskussionunclassified